Mobile Phones in Classrooms and in Professor-Student Communication: Ukrainian, Omani, and U.S. American College Students’ Perceptions and Practices - Alla V. Tovares (International Journal of Interactive Mobile Technologies, 2021)
The unprecedented expansion of wireless technologies and the global pandemic of 2020-2021, which forced many educational establishments out of traditional face-to-face and into online instructional environments, have created an urgency for achieving a better understanding of the various education-related uses of mobile phones, and students’ attitudes toward them, worldwide. We conducted a questionnaire-based study to explore college undergraduate students’ perceptions and uses of mobile phones, with a focus on instructor-student communication and classroom use, across three diverse cultural contexts: Ukraine, Oman, and the United States. Based on our findings, we suggest that conceptualizing mobile phones as cultural tools and situating their use within cultural discourses illuminates how – and explains why – mobile phones are not “the same” tools for all students. The findings offer insights into students’ (developing) perspectives on uses of mobile phones, and provide grounds from which to formulate productive, and culturally appropriate, means of using them for educational purposes.